Self Assembly of Patchy Anisotropic Particle Forming Free Standing Monolayer Film. Issue 3 (11th January 2023) - Varma, Vikki Anand; Kritika,; Singh, Jaskaran; Babu, Sujin B.
Abstract: Synthesizing thin films using self assembly is one of the important challenges which needs to be addressed for making engineered material using colloidal particle, necessary for creating novel material for photonic, filtration application, etc. Here, a simple model of prolate ellipsoidal particle with two directional bonds is presented and the phase behavior is studied using NVT and NpT Monte Carlo simulation. It is observed that for anisotropic particles with patches two different type of 3D ordered structures are formed along with thermodynamically stable monolayer which is confirmed using thermodynamic integration. The phase diagram shows that the desired 2D super structure can be created using simple self assembly route. Abstract : In the present work the phase diagram of ellipsoidal particles with two patches is established using simulations. Here, the presence of four different phases is reported, namely the fluid, Type I HCP crystal, Type II HCP crystal, and a monolayer phase. The Type I and Type II crystals vary from each other only in the relative arrangement of it stacking.